2023
DOI: 10.3390/jpm13030403
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Risk Model Based on Nature Killer Cells for Serous Ovarian Cancer

Abstract: Nature killer (NK) cells are increasingly considered important in tumor microenvironment, but their role in predicting the prognosis of ovarian cancer has not been revealed. This study aimed to develop a prognostic risk model for ovarian cancer based on NK cells. Firstly, differentially expressed genes (DEGs) of NK cells were found by single-cell RNA-sequencing dataset analysis. Based on six NK-cell DEGs identified by univariable, Lasso and multivariable Cox regression analyses, a prognostic risk model for ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Hence, we wanted to evaluate if the PTGS2 / CTLA4 ratio also determines the infiltration and cytotoxic capacity estimate in HGSOC. For this, we considered the recent publication by Zhang et al [ 54 ]. In that work, the authors proposed several genes associated with risk prognosis models through differential expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we wanted to evaluate if the PTGS2 / CTLA4 ratio also determines the infiltration and cytotoxic capacity estimate in HGSOC. For this, we considered the recent publication by Zhang et al [ 54 ]. In that work, the authors proposed several genes associated with risk prognosis models through differential expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple mechanisms of killing, low risk of CRS, GvHD, and neurotoxicity make NK cells an attractive platform for adoptive cell therapy-based approaches, and their translation in early clinical trials has demonstrated safety and promising preliminary results in multiple cancers. In EOC, the presence of NK cells correlates with improved survival, and a prognostic risk model based on differentially expressed genes of NK cells in EOC samples has recently been reported, further underscoring the importance of NK cellmediated antitumor activity (16,17).…”
Section: Introductionmentioning
confidence: 95%